Adjunctive Brivaracetam in People with Epilepsy and Intellectual Disability: Evidence from the BRIVAracetam Add-On First Italian netwoRk Study - Simona Lattanzi; Laura Canafoglia; Maria Paola Canevini; Sara Casciato; Emanuele Cerulli Irelli; Valentina Chiesa; Filippo Dainese; Giovanni De Maria; Giuseppe Didato; Giancarlo Di Gennaro; Giovanni Falcicchio; Martina Fanella; et al. (Neurology and Therapy)
Abstract Introduction Subjects with intellectual disability are usually excluded from clinical trials and there is limited evidence-based guidance for the choice of antiseizure medications in this vulnerable population. The study explored the effectiveness of brivaracetam (BRV) in people with epilepsy and intellectual disability. Methods BRIVAracetam add-on First Italian netwoRk Study (BRIVAFIRST) was a 12-month retrospective, multicenter study including adults prescribed adjunctive BRV. Main outcomes included the rates of seizure‐freedom, seizure response (≥ 50% reduction in baseline seizure frequency), and treatment discontinuation. The occurrence of adverse events (AEs) was also considered. Analyses by the presence and severity of intellectual disability were performed. Results Subjects with intellectual disability were 253 (24.6%) out of 1029 participants. The 12-month rates of seizure freedom were 18.4% and 10.3% in participants without and with intellectual disability, respectively; the corresponding values for seizure response were 40.0% and 28.9%. Intellectual disability was not an independent predictor of seizure outcomes. The rates of treatment discontinuation were 25.8% and 26.4% in participants without and with intellectual disability. respectively. There were no statistically significant differences in the rates of any AEs, somnolence, nervousness/agitation, and aggressiveness by the presence and degree of intellectual disability. Conclusion Brivaracetam can be a suitable treatment option and offer opportunities for clinical improvement in subjects with intellectual disability and uncontrolled seizures.